Sistem Monitoring Total Dissolved Solid (TDS) pada Lower Basin Cooling Tower Menggunakan Sensor Berbasis Internet di Bandar Udara Internasional Yogyakarta – Kulon Progo - Kurnianto, Benny; Mediaswati, Cristina Novi; Nugroho, Hasbi Ahmad; Fajar, Arvan; Davin, Nayandra; Cheisa, Salsa (Program Studi Teknik Mekanikal Bandar Udara, 2023)
The quality of cooling water used in cooling towers can affect operational efficiency as well as the service life of the equipment. Therefore, an accurate and real-time monitoring system is needed to monitor Total Dissolved Solid (TDS) in cooling water. This system is designed to provide accurate and real-time information about TDS levels in cooling water, enabling operational personnel to take necessary preventive and corrective actions in a timely manner. This allows operational personnel to detect changes in water quality early and take necessary action to prevent damage to the cooling system. In addition, the system can also assist in effective maintenance planning, by enabling the identification of changing trends in water quality over time.